THE CONTRIBUTION OF THE JOURNALS: JTEFS AND DCSE ON A SUSTAINABLE DEVELOPMENT OF THE REGION - Ilisko, Dzintra; Skrinda, Astrida; Pipere, Anita (Via Latgalica, 2017)
The report reveals the contribution of two international UNESCO/ UNITWIN Chair’s peer-reviewed journals – “Discourse and Communication for Sustainable Education” (DCSE) and “Journal of Teacher Education for Sustainability” (JTEFS) to sustainable development of Latgale. They are international, cross-disciplinary, scholarly and open access journals focusing on diverse aspects of environmental, cultural, economic and social sustainability thus enabling one to constructively and creatively address present and future global challenges in creating more sustainable and resilient societies. Both journals aim to respond to the priorities set by the United Nations Decade of Education for Sustainable Development and the Global Action Programme as implemented in LATGALE and in the partner countries. The study reflects on the thematic scope of the two journals that centres on reorienting education towards the goal of sustainable education and sustainable community in Latgale, Latvia, Europe and beyond. In order to respond to the challenges of global community that we are facing today, the research published in both journals suggests how education can contribute to overcoming the current crises in education and community, as well as offers strategies and ways of dealing with it sustainably and responsibly in Latgale. Education for sustainable development (ESD) includes more than knowledge related to the environment, economy, culture and society. It also addresses learning perspectives, strategies and values that guide and motivate people to seek sustainable livelihoods, participate in a democratic society and live in a sustainable manner. ESD also involves studying both local and global issues. The research offers the study of JTEFS contribution to meeting different views, ideas and research to promote further development of studies and practice of teacher education in all areas of formal and non-formal education in relation to sustainability. DCSE is an international, peer-reviewed journal that provides a platform for examination of policies, theories and practices related to the discourse and communication for sustainable education. Since contemporary discourse study has extended its field to the study of multifaceted contexts of discourse, it integrates a broader study of the phenomena of communication in relation to sustainable education. The diversity of the journal is apparent in the variety of its theories, methods and approaches, thus avoiding the frequent limitation to one school, approach or academic branch.